Preoperative vestibular assessment protocol of cochlear implant surgery: an analytical descriptive study - Roseli Saraiva Moreira Bittar; Eduardo Setsuo Sato; Douglas Jósimo Silva Ribeiro; Robinson Koji Tsuji (Brazilian Journal of Otorhinolaryngology)
Abstract Introduction: Cochlear implants are undeniably an effective method for the recovery of hearing function in patients with hearing loss. Objective: To describe the preoperative vestibular assessment protocol in subjects who will be submitted to cochlear implants. Methods: Our institutional protocol provides the vestibular diagnosis through six simple tests: Romberg and Fukuda tests, assessment for spontaneous nystagmus, Head Impulse Test, evaluation for Head Shaking Nystagmus and caloric test. Results: 21 patients were evaluated with a mean age of 42.75 ± 14.38 years. Only 28% of the sample had all normal test results. The presence of asymmetric vestibular information was documented through the caloric test in 32% of the sample and spontaneous nystagmus was an important clue for the diagnosis. Bilateral vestibular areflexia was present in four subjects, unilateral arreflexia in three and bilateral hyporeflexia in two. The Head Impulse Test was a significant indicator for the diagnosis of areflexia in the tested ear (p = 0.0001). The sensitized Romberg test using a foam pad was able to diagnose severe vestibular function impairment (p = 0.003). Conclusion: The six clinical tests were able to identify the presence or absence of vestibular function and function asymmetry between the ears of the same individual.